Previniendo desastres naturales creando un plan de emergencia - Herrera Rosas, Edward David (2019)
This work helps prevent natural disasters, creating an emergency plan and minimizing material and human damage during the three moments: before, during and after, it is also useful for educational institutions to teach their students how to react when a problem occurs. natural disaster.